Microfiber-based saturable absorber incorporating graphene polymer nanocomposites for femtosecond pulse generation - Ng, Eng Khoon (2017)
Since the advent of pulse laser, the duration of shortest pulse has rapidly changed from the nanosecond (10-9 s) to the femtosecond (10-12 s) regime. Ultrashort light pulses can be generated using mode-locking techniques which contain either an active element or a nonlinear passive element in a laser resonator. The current commercialized ultrashort laser technologies are typically based on semiconductor saturable absorber mirror (SESAM) which requires complex fabrication method and fine tuning between the fiber pigtail and SESAM to generate mode-locking. A number of fiber-based saturable absorber papers have been reported to overcome this problem. In line with this advancement, this research work focuses on microfiber-based saturable absorber incorporating graphene composite as a nonlinear component in different operating wavelength regions of laser cavity. The first process in the experimental work is to fabricate a saturable absorber that is able to generate femtosecond pulse in a ring cavity. The graphene nanoparticles are prepared through liquid phase exfoliation method. Then, the nanoparticles are synthesized with PDMS to produce a graphene composite. Finally, the graphene composite is coated on a prepared microfiber through dip coating method. The prepared microfiber has waist diameter of 10 μm, waist length of 0.5 mm, and total length of 60.5 mm. The quality of coating on the microfiber is characterized through Raman spectroscopy, field effect scanning electron microscope and energy dispersive X-ray spectroscopy. The fabricated saturable absorber has transmission loss of less than 4.6 dB and modulation depth of 9.6%. In this research, a ring-configuration erbium-doped fiber laser (EDFL) setup is employed to generate optical pulses with the assistance of the fabricated inline graphene composite saturable absorber. This saturable absorber initiates ultrashort pulse signal with observation of multiple Kelly’s sidebands, output pulse train with constant round trip time and pulse width within femtosecond range. The generation of optical pulses is performed in two wavelength ranges; C-band and L-band. For each band, the dispersion is optimized to ensure that the fiber laser produces soliton pulses. The soliton pulse is observed with the presence of Kelly’s sidebands at the laser output. For C-band, the fabricated saturable absorber is placed in a ring cavity with the employment of 5 m HP980 erbium-doped fiber (EDF). The mode-locked operation is observed at 33.54 mW pump power. The output pulse has a central wavelength of 1557.05 nm with 3 dB spectral width of 5.92 nm. The generated soliton pulse has pulse duration of 631 fs, repetition rate of 9.65 MHz and time bandwidth product of 0.46. For L-band fiber laser, the same saturable absorber is utilized with 17 m long LIEKKI EDF. The mode-locked threshold pump power is obtained at 39.6 mW. The output laser is generated at 1599.56 nm with 3 dB spectral width of 5.773 nm. Stable mode-locked pulse with pulse duration of 568 fs, repetition rate of 5.76 MHz, and time bandwidth product of 0.38. In conclusion, the fabricated graphene composite microfiber has been proven to function capably as saturable absorber in C-band and L-band. This shows that it can operate in wide operating wavelength range. The quality of optical pulse in the range of femtosecond indicates its ability to generate ultrashort pulses with strong saturation absorption. The time bandwidth product above 0.315 denotes the operation is close to ideal Fourier transform limited pulse. Overall, the results validate the reliability of the proposed method to produce microfiber-based saturable absorber.